CT characteristics of uterine and vaginal mesenchymal tumours in dogs. (11th January 2021) - Barozzi, M. C. M.; Saba, C. F.; Gendron, K. P.
Abstract : Objectives: To describe the CT characteristics of uterine and vaginal mesenchymal tumours in dogs and to discuss imaging findings of the tumour types encountered. Materials and Methods: Retrospective study on female dogs with confirmed histological diagnosis of uterine and vaginal mesenchymal tumours and available CT images. Results: 120 records obtained through a medical record search were manually evaluated for eligibility, and 11 dogs presenting masses associated with the genital tract were identified. Of these 11 dogs, 7 dogs met the inclusion criteria and were included in the study. A clear degree of overlap was present between measurements of maximal diameter of benign and malignant tumours; however, malignant neoplasms tended to occupy a larger portion of the pelvic canal. Objective measurements of length suggest that malignant tumours were longer than benign forms. Bone involvement was only observed with malignancy. Clinical Significance: Although CT is likely to play a limited role in the advanced workup of uterine and vaginal mesenchymal neoplasms, CT may represent a more accessible diagnostic tool than MRI and results of this study may help imagers familiarise themselves with their appearances.